Investigating the dual role of mitochondrial and nuclear genome variants in pediatric cardiomyopathies - M. Arda Temena; Ebru Erzurumluoglu Gokalp; Ezgi Susam; Duygu Cinar; Hikmet Kiztanir; Pelin Kosger; Beyhan Durak Aras; Sevilhan Artan; Oguz Cilingir (Scientific Reports)
Abstract Mitochondrial defects can lead to cardiomyopathies, which can be particularly severe in children. However, many cases of pediatric cardiomyopathy have no known etiology. To address this, we sought to explore if mitochondrial genome defects might be a contributor, as this could offer insights into disease mechanisms and guide targeted interventions. We first sequenced cardiomyopathy-related genes in twenty-seven pediatric patients diagnosed with primary non-syndromic cardiomyopathy and performed whole mtDNA sequencing in both patients and thirty-one healthy controls. The initial sequencing identified pathogenic variants in seven patients but subsequent mtDNA sequencing revealed additional insights. Specifically, a variant in FOXRED1, encoding FAD-dependent oxidoreductase domain-containing protein-1 which functions in mitochondrial complex I stability, and another variant in cytochrome c oxidase-I, MT-CO1, crucial for aerobic metabolism, were identified in two siblings with hypertrophic cardiomyopathy. In another case with hypertrophic cardiomyopathy, a variant in cytochrome b, MT-CYB, is likely a key factor in the abnormal contraction of cardiac muscle contraction. Furthermore, a novel 12 S rRNA variant was found in a patient with left ventricular non-compaction, and this offers a promising explanation for the pathogenesis, given the gene’s high expression in the left ventricle. Taken together, mtDNA variants act synergistically with others, potentially disrupting myocardial bioenergetics.